Boosted Influenza-Specific T Cell Responses after H5N1 Pandemic Live Attenuated Influenza Virus Vaccination - Peng, YanChun; Wang, Beibei; Talaat, Kawsar; Karron, Ruth; Powell, Timothy J.; Zeng, Hui; Dong, Danning; Luke, Catherine J.; McMichael, Andrew; Subbarao, Kanta; Dong, Tao (Frontiers in Immunology, 2015)
Background: In a phase I clinical trial, a H5N1 pandemic live attenuated influenza virus (pLAIV) VN2004 vaccine bearing avian influenza H5N1 HA and NA genes on the A/Ann Arbor cold-adapted vaccine backbone displayed very restricted replication. We evaluated T cell responses to H5N1 pLAIV vaccination and assessed pre-existing T cell responses to to determine whether they were associated with restricted replication of the H5N1 pLAIV. Method: ELISPOT assays were performed using pools of overlapping peptides spanning the entire H5N1 proteome and the hemagglutinin (HA) proteins of relevant seasonal H1N1 and H3N2 viruses. We tested stored PBMCs from 21 study subjects who received two doses of the H5N1 pLAIV. The PBMCs were collected 1 day before and 7 days after the first and second pLAIV vaccine doses, respectively. Result: T cell responses to conserved internal proteins M and NP were significantly boosted by vaccination (p=0.036). In addition, H5N1 pLAIV appeared to preferentially stimulate and boost pre-existing seasonal influenza virus HA-specific T cell responses that showed low cross-reactivity with the H5 HA. We confirmed this observation by T cell cloning and identified a novel HA-specific epitope. However, we did not find any evidence that pre-existing T cells prevented pLAIV replication and take. Conclusion: We found that cross-reactive T cell responses could be boosted by pLAIV regardless of the induction of antibody. The impact of the “original antigenic sin” phenomenon in a subset of volunteers, with preferential expansion of seasonal influenza-specific but not H5N1-specific T cell responses merits further investigation.